Studies on application of hanging capsule over plant in tobacco seed reproduction and multiplication - DAI Fei; ZHOU Wei-jun (浙江大学学报. 农业与生命科学版, 2005)
This paper compared the hanging capsule over plant with the routine method in tobacco seed reproduction and multiplication. The results showed that tobacco seeds produced by hanging capsule over plant and the routine method had the similar germination percentage. But the former had the higher germination energy which was increased by 11.67% than routine one with the lower CV (2.23%) for the naked seeds. Its germination energy was also increased by 8.14% than routine one with the lower CV (1.76%) for the coated seeds. The plants using hanging capsule over plant had less black and brown seeds (less than 5%), and showed the uniform maturity, The seeds were more bright and maintained the characteristics of variety itself. Meanwhile, hanging capsule over plant had the advantage of easy operation, practical convenience and high economic benefits.